Utilizing GPS data tracking design for stopped truck analysis in an industrial loading process - Osman, Khairuddin; Thangavelloo, Vishanthini; Zainuddin, Norzahirah; Kanda, Takefumi (Penerbit Universiti Teknikal Malaysia Melaka, 2024)
Economic growth has become essential for improving people’s livelihoods, particularlyas more enterprises are established. This expansion has increased the demand for transportation, where timely delivery of goods is crucial forthe success ofgrowing businesses. Consequently, vehicles have become a vital componentofthe logisticschain, transportingitems from one location to another. However, traffic delays often hinder timely deliveries, and administrators struggle to locate trucks during unexpected stops. Additionally, some truck drivers waste time, causing unnecessary delivery delays and increasing operating costs. This study proposesa solution thatintegratesan RFID sensor module toaddress traffic congestion issues at loading bays and a GPS module with TTGO TCALL ESP 32 to track the whereabouts of trucks.This approach aims to improve operational efficiency, reduce costs and streamline the logistics process.